A "sandwich" cell culture platform with NIR-responsive dynamic stiffness to modulate macrophage phenotypes. (12th February 2021) - Yuan, Peiqi; Luo, Yilun; Luo, Yu; Ma, Lie
Abstract : A "sandwich" cell culture platform with the ability to be rapidly transformed from lower stiffness to higher stiffness under near-infrared (NIR) irradiation and to induce the phenotypic transformation from M2 to M1 sequentially. Abstract : Considering the key roles of macrophages in tissue repair and immune therapy, designing smart biomaterials able to harness macrophage phenotypes on demand during the healing process has become a promising strategy. Here, a novel "sandwich" cell culture platform with near-infrared (NIR) responsive dynamic stiffness was fabricated to polarize bone marrow-derived macrophages (BMDMs) in situ for revealing the relationship between the macrophage phenotype and substrate stiffness dynamically. Under NIR irradiation, calcium ions (Ca 2+ ) diffused through the middle layer of the IR780-mixed phase change material (PCM) due to the photothermal effect of IR780, resulting in an increase of hydrogel stiffness in situ by the crosslinking of the upper layer of the hyaluronic acid-sodium alginate hydrogel (MA-HA&SA). The up-regulation of inducible nitric oxide synthase (iNOS) and tumor necrosis factor-α (TNF-α) was quantified by immunostaining and enzyme-linked immune sorbent assay (ELISA), respectively, indicating the transformation of macrophages from the anti-inflammatory to pro-inflammatory phenotype under dynamic stiffness. The nuclear Yes-associated-protein (YAP) ratio positively correlated with the shift of the macrophage phenotype. The modulation of macrophage phenotypes by stiffness-rise without the stimuli of cytokines offers an effective and noninvasive strategy to manipulate immune reactions to achieve optimized healing or therapeutic outcomes.